Studi Komunikasi Simbolis Berbasis Korpus tentang Cinta dalam Lagu-Lagu Tulus - Utami, Dewi (Jurnal ILMU KOMUNIKASI, 2025)
This study analyzes love that is communicated in Tulus’ song lyrics using corpus linguistics and close reading. Through the frameworks of Coordinated Management of Meaning (CMM) and Lee’s love typology, the findings show that love is conveyed through implicit symbolism rather than direct declarations. Storge, agape, and pragma are the dominant love styles reflected in the lyrics, emphasizing relational and reflective forms. The study highlights that, love in high-context communication cultures is constructed through narrative and layered meaning coordination. This confirms the significance of symbolic approaches in understanding emotional expression in Indonesian pop music.